2008
DOI: 10.1021/ic800805r
|View full text |Cite
|
Sign up to set email alerts
|

First Row Transition Metal Ion-Assisted Ammonia−Borane Hydrolysis for Hydrogen Generation

Abstract: Ammonia-borane (AB) hydrolysis for the generation of hydrogen has been studied using first row transition metal ions, such as Co (2+), Ni (2+), and Cu (2+). In the cases of cobalt- and nickel-assisted AB hydrolysis, amorphous powders are formed that are highly catalytically active for hydrogen generation. Annealing of these amorphous powders followed by powder X-ray diffraction measurements revealed the presence of Co(0) and Co 2B and Ni(0) and Ni 3B, respectively. On the other hand, copper-assisted AB hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(119 citation statements)
references
References 33 publications
1
116
0
Order By: Relevance
“…Hydrogen is a next-generation fuel that is attractive because it cleanly burns and is thus environment friendly [1]. However the large-scale use of hydrogen is hindered by the difficulty of storing and transporting it in compressed or liquefied form because of its low density [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen is a next-generation fuel that is attractive because it cleanly burns and is thus environment friendly [1]. However the large-scale use of hydrogen is hindered by the difficulty of storing and transporting it in compressed or liquefied form because of its low density [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…However the large-scale use of hydrogen is hindered by the difficulty of storing and transporting it in compressed or liquefied form because of its low density [1,2]. Thus, finding a safe and efficient storage material is necessary [3].…”
Section: Introductionmentioning
confidence: 99%
“…[33] We found that in all the cases, the nanoparticles obtained were quite monodisperse, well separated, and crystalline in nature. Cu, Ag, and Au nanoparticles of average sizes 4.3, 4.7 and 5.1 nm, respectively, were obtained when CuSO 4 ·2 H 2 O, AgNO 3 , and HAuCl 4 ·3 H 2 O were used as metal precursors.…”
Section: Aqueous Mediummentioning
confidence: 72%
“…Various catalysts with excellent catalytic performance have been developed [52][53][54][55][56][57][58][59][60][61][62][63]. These include noble metal based catalysts such as Pt, Ru, Rh, Pd, Pt and Au supported on alumina; combinations of Pt with Ir, Ru, Co, Cu, Sn, Au and Ni supported on carbon, Rh(0) nano-clusters [52][53][54][55][56][57]; and also non-noble metal based catalysts such as Ni and Co on alumina, and Ni and Co nano-particles, Cu/Cu2O, Poly(N-vinyl-2-pyrrolidone) (PVP) stabilized Ni, NiSiO2 and Fe-Ni alloys [58][59][60][61][62][63]. Unfortunately, most of the aforementioned catalysts, except for the magnetic Fe-Ni alloy catalyst, are difficult to use repeatedly in solution because they are in a powdery form or are supported weakly on a substrate.…”
Section: Hydrogen Production From Ammonia Boranementioning
confidence: 99%